Uniqueness of an Orthogonal 2-Handle Pair on a Surface-Link (Contemporary Mathematics, 2023)
The proof of uniqueness of an orthogonal 2-handle pair on a surface-link is given from the viewpoint of a normal form of 2-handle core disks. A version to an immersed orthogonal 2-handle pair on a surface-link is also observed.
Keywords: surface-link, orthogonal 2-handle pair